Practical model of low-volume paddling-based sprint interval training improves aerobic and anaerobic performances in professional female canoe polo athletes - Sheykhlouvand, M.; Khalili, E.; Gharaat, M.; Arazi, H.; Khalafi, M.; Tarverdizadeh, B. (The Journal of Strength and Conditioning Research, 2018)
Brief, intense exercise training using running and cycling as exercise interventions may induce aerobic and anaerobic adaptations in athletes from a wide range of sports. However, this has not been studied extensively for those sports in which the upper body is predominantly involved. Our purpose was to examine the effects of kayak paddling-based sprint interval training (SIT) on cardiorespiratory fitness and anaerobic performance. Sixteen professional female canoe polo athletes (age = 27.6 ± 1.9 years; height = 165.7 ± 5.2 cm; body mass = 62.6 ± 8.5 kg; body mass index = 22.8 kg/m; body fat = 23.8 ± 4.9%) were randomized to either an intense exercise training consisting of sets of 5 × 5-second maximum sprint efforts interspersed by a 10-second recovery between each sprint (3, 4, 5, and 6 sets/session from first to fourth week, respectively, with 3 minutes of rest between each set), performed 3 times per week for 4 weeks (n = 8), or a usual training control group (n = 8). Before and after the training period, aerobic and anaerobic measurements were assessed using a kayak specific test and Wingate protocol, respectively. Training increased VO2peak, O2 pulse, anaerobic threshold, peak, and mean power output in the SIT group compared with the control group (p = 0.05) who showed no changes in these variables when tested 4 weeks apart without SIT. Paddling-based SIT was a potent stimulus and time-efficient strategy to induce rapid adaptations in aerobic and anaerobic performances in professional female canoe polo athletes who can use this training method to achieve fitness in a short period.